Psychological Study of Stress Levels among Secondary School Students with Albinism in Tanzania - George Mwala; Suitbert Lyakurwa (Universitas Pendidikan Indonesia (UPI), 2022)
This study investigated the psychological situation of secondary school students with albinism in Tanzania. Particularly, the study focuses on the levels of stress among students with albinism. The study was approached quantitatively and a sample of 80 students with albinism in the Shinyanga region in Tanzania was surveyed. Data were collected using questionnaires and analyzed by frequencies and percentages. Further, a t-test was used to test the hypothesis. The results indicated that 52.6% had the highest, 37.53% had moderate and 21.48% had the lowest level of stress. However, in terms of sex, male students demonstrated a bit higher level of stress than female students and differed significantly. It is concluded that in general, secondary school students with albinism had a moderate level of stress. The findings inform education stakeholders to incorporate training and counseling services to assist students in addressing the levels of stress.